Exploring the responsiveness of goal attainment scaling in relation to number of goals set in a sample of hemophilia-A patients - Lisa McGarrigle; Jonathan C. Roberts; Michael Denne; Kenneth Rockwood (SpringerOpen, 2019)
Abstract Purpose Guidelines for the use of goal attainment scaling (GAS) recommend that the patient specify at least three goals. Even so, this may not always be feasible or align with patient preferences. Investigations into the psychometric properties of GAS using three or more goals largely support its reliability, validity, and responsiveness compared with standard measures. As evaluations of responsiveness rely on variability estimates, this metric may be impacted when GAS is based on fewer than three goals. For this reason, we investigated the responsiveness of one- and two-goal GAS. Methods Secondary analyses were conducted on data from a mixed sample of pediatric, adolescent and adult subjects with hemophilia A. The standardized response mean (SRM) and its 95% confidence intervals (CI) were used to assess responsiveness of one- and two-goal GAS at six and twelve weeks. Results Both one-goal and two-goal GAS demonstrated similar responsiveness to change at 6-week (Patient-Rated GAS: one-goal SRM [95% CI] = 0.70 [0.45-1.08], two-goal = 0.96 [0.68-1.30]; Clinician-Rated GAS: one-goal = 1.26 [0.81-1.77], two-goal = 1.01 [0.73-1.32]) and 12-week follow-up (Patient-Rated GAS: one-goal SRM [95% CI] = 1.14 [0.53-1.71], two-goal = 1.35 [0.92-1.82]; Clinician-Rated GAS: one-goal = 1.71 [1.12-2.30], two-goal = 1.48 [1.02-2.02]). Larger SRMs were observed for clinician-rated GAS, but all were within the rubric of a large effect size. Conclusions One-goal GAS is responsive to change in a clinical population. Further research is recommended in a larger sample where responsiveness of one- and multiple-goal GAS can be compared